2009
DOI: 10.1158/1055-9965.epi-09-0601
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Low Penetrance Susceptibility Loci in a Dutch Familial Colorectal Cancer Cohort

Abstract: Recent genome-wide association studies have identified several loci that confer an increased risk of colorectal cancer (CRC). We studied the role of the 8q24.21 (rs6983267), 18q21.1 (rs12953717), 15q13.3 (rs4779584), 11q23.1 (rs3802842), 8q23.3 (rs16892766), and 10p14 (rs10795668) risk variants in a series of 995 Dutch CRC cases and 1340 controls. The CRC cases were selected on basis of having a family history of CRC and/or early-onset disease. The detailed clinical and molecular data available on the cases al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 28 publications
7
58
2
Order By: Relevance
“…To the best of our knowledge, several studies corroborated the role of rs12953717 polymorphism in cancer susceptibility (Broderick et al, 2007;Tomlinson et al, 2008;Curtin et al, 2009;Middeldorp et al, 2009;Pittman et al, 2009;Slattery et al, 2010;Ho et al, 2011;Li et al, 2011). According to previous cancer-susceptibilitystudies which mainly revealed the remarkable association between the SMAD7 SNP and the risk of CRC, our study demonstrated that allele T at rs12953717 can increase the risk of CRC.…”
Section: Discussionsupporting
confidence: 77%
“…To the best of our knowledge, several studies corroborated the role of rs12953717 polymorphism in cancer susceptibility (Broderick et al, 2007;Tomlinson et al, 2008;Curtin et al, 2009;Middeldorp et al, 2009;Pittman et al, 2009;Slattery et al, 2010;Ho et al, 2011;Li et al, 2011). According to previous cancer-susceptibilitystudies which mainly revealed the remarkable association between the SMAD7 SNP and the risk of CRC, our study demonstrated that allele T at rs12953717 can increase the risk of CRC.…”
Section: Discussionsupporting
confidence: 77%
“…DNA from index patients with colorectal polyposis 15 and familial CRC 16 was analysed for POLE NM_006231.2:c.1270C4G, p.(Leu424Val) and POLD1 NM_002691.1:c.1433G4A, p.(Ser478Asn). Leucocyte DNA from 485 polyposis cases was included.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…These samples were described before, only DNA that passes quality check was included in the study. 16 The study was approved by the local medical ethical committee of the Leiden University Medical Center (P01-019).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…The SNP rs6983267 on chromosome 8q24. 21 was the first to be identified as a common susceptibility variant for CRC by three GWAS in the United Kingdom, Canada, and Scotland (7)(8)(9). The second SNP rs4939827 on 18q21.1 harboring SMAD7, a strong candidate gene, has subsequently been identified by a GWAS in the United Kingdom and further confirmed by another GWAS in Scotland (10,11).…”
Section: Introductionmentioning
confidence: 94%